AN OVERVIEW OF HISTORICAL SOURCES OF MONGOL HISTORY - Muhammad Nabeel Musharraf; Zain ul Abdin Sodhar (دی اسکالر)
The credibility of research in history depends on the credibility of sources referred to in the process and the way they are interpreted. Accordingly, it is imperative, firstly, to select the right sources, and secondly, to thoroughly analyze and question them. The situation, in many instances, gets aggravated when researchers find contradicting information from various sources. Such a situation necessitates paying due attention to the contexts in which these works were written, the potential influences that the authors may have faced, and the way in which such works were transmitted. This paper is an attempt make a contribution in this direction in relation to a few key primary and secondary sources of Mongol history that can extremely vital in reconstructing their times, their mindset, their empire and the horrific invasions they are known for. We have presented a brief overview of 15 important classical historical sources that shed light on the Mongol history and their conquests. Though most of the major events appear to be mentioned in these works, however, while reviewing these works, difference can be noticed in terms of author’s opinions and support (or lack thereof) for those events and underlying decisions from various players appearing in the picture. We also see a tint of political influence in these works. Some of the works are known to have mistakes in terms of certain specific information about the events and persons involved. Historical sources selected for this study were either written as the relevant events were unfolding, or written within a few centuries after the events took place. In these sources, we also notice that some of the authors were the direct eyewitnesses of the incidents whereas others relied on second or third-hand information. Accordingly, it becomes important for researchers to understand these factors in order to correctly reference from these works and contribute to the body of knowledge on the subject in a meaningful and healthy way.